Prevalence and prognosis of aortic valve diseases in patients hospitalized with heart failure with mildly reduced ejection fraction - Schupp, Tobias; Abel, Noah; Schmidberger, Moritz; Höpfner, Mila Kathrin; Schmitt, Alexander; Reinhardt, Marielen; Forner, Jan; Lau, Felix; Akin, Muharrem; Rusnak, Jonas; Akın, Ibrahim; Behnes, Michael (European journal of heart failure, 2024)
Aims Data regarding the characterization and outcomes of patients with heart failure (HF) with mildly reduced ejection fraction (HFmrEF) is scarce. This study investigates the characteristics and prognostic impact of native aortic valve diseases (AVD) in patients with HFmrEF. Methods and results Consecutive patients hospitalized with HFmrEF (i.e. left ventricular ejection fraction 41-49% and signs and/or symptoms of HF) were retrospectively included at one institution from 2016 to 2022. The prognostic impact of native aortic valve stenosis (AS), aortic valve regurgitation (AR) and mixed AVD (MAVD) was investigated for the primary endpoint of long-term all-cause mortality during a median follow-up of 30 months. Kaplan-Meier, univariable and multivariable Cox proportional analyses were applied. From a total of 2106 patients hospitalized with HFmrEF, the prevalence of AS and AR was 16.5% and 31.2%, respectively (MAVD 7.8%). The presence of moderate/severe AS was associated with a higher risk of long-term all-cause mortality (44.8% vs. 28.7%; p = 0.001) and HF-related rehospitalization (18.6% vs. 12.0%; p = 0.001), even after multivariable adjustment (mortality: hazard ratio [HR] 1.320; 95% confidence interval [CI] 1.035-1.684; p = 0.025; HF-related rehospitalization: HR 1.570; 95% CI 1.101-2.241; p = 0.013). Interestingly, even mild AS was associated with increased risk of long-term all-cause mortality compared to patients without AS (HR 1.477; 95% CI 1.101-1.982; p = 0.009). In contrast, the presence of AR was not associated with long-term outcomes after multivariable adjustment. Conclusions The presence of AS, but not AR, was independently associated with increased risk of all-cause mortality and HF-related rehospitalization in patients with HFmrEF. Even milder stages of AS were associated with impaired prognosis.
Zuerst veröffentlicht: 19. Juni 2024
Gesehen am 20.11.2024